The impact of learner background variables on academic burnout in online vs. face-to-face classes among students of Shiraz University of Medical Sciences having English courses - Kashefian-Naeeini, Sara; Zarifsanaiey, Nahid; Mehrabi, Manoosh (Frontiers in Psychology, 2025)
IntroductionAcademic burnout is a universal phenomenon that has impacted many students in different educational settings. The present study attempted to compare the academic burnout that students of Shiraz University of Medical Sciences (SUMs) faced in online vs. face-to-face environments. It also sought to determine the effects of learner background variables of age, academic achievement, and degree programs on selected students’ academic burnout.MethodsThe power analysis was performed using gpower to determine the required sample size, and 257 participants taking their General English courses were involved in the study. Then, cluster sampling was used to select a random sample from the students taking an English course at SUMS. An online modified version of the Maslach Burnout Inventory (MBI), measuring participants’ academic burnout, was used to represent students’ reported burnout.ResultsA paired samples t-test was performed to compare reported academic burnout in online classes vs. face-to-face environments, indicating significant differences in academic burnout between the two modalities (online vs. face-to-face), with lower levels of burnout reported for online environments. Moreover, a multivariate analysis of variance (MANOVA) was performed to determine the effects of the learner background variables of academic achievement and age on academic burnout, which manifested significant differences in burnout in face-to-face learning environments for students of different age groups. Likewise, it was illuminated that academic achievement influenced students’ burnout in face-to-face environments, as high achievers experienced significantly lower academic burnout than moderate achievers. A robust MANOVA of Pillai’s trace also indicated no significant differences between Bachelor of Science and Professional Doctorate students across the dependent variables of academic burnout in online vs. face-to-face environments.DiscussionEducators must balance workload, seek regular student feedback about lesson pace and delivery, and avoid overloading students with overdemanding assignments and projects or setting unrealistic goals and expectations. The present study has cast light on the multifaceted nature of burnout and the factors that impact academic burnout in educational settings. It can pave the way for education practitioners to follow appropriate strategies and macro-level policies to mitigate learner burnout.